Legal Consequences of Opening Access to Financial Information of Customer Data for Tax Purposes Based on Indonesian Law - Kristi Emelia Pasaribu; Budiman Ginting; Sunarmi Sunarmi; Mahmul Siregar (International Journal Reglement & Society (IJRS), 2022)
The enactment of Law Number 9 of 2017 concerning Government Regulation in Lieu of Law Number 1 of 2017 concerning Access to Financial Information for Tax Purposes Being this law is the first step in tax reform to improve the taxpayer database and also transparency of the tax potential that exists in each taxpayer. This law is the commitment of the State of Indonesia to participate in the G20 international agreements in the field of taxation in order to realize the Automatic Exchange of Financial Account Information (AEOI) financial information exchange and is expected to help strengthen Indonesia's tax system towards a more modern direction and increase awareness of mandatory taxes in fulfilling their tax obligations. The research method is normative juridical, which is descriptive analytical with data collection techniques from library research. Data analysis was carried out using a qualitative normative method, where this research was classified as normative which was complemented by a comparison of secondary data research. From the results of the study, it is known that the legal consequences of opening access to financial information on customer data after the issuance of Law no. 9 of 2017 concerning Stipulation of Government Regulation in Lieu of Law No. 1 of 2017 concerning Access to Financial Information for Tax Purposes Being a law is for the tax party, namely the Directorate General of Taxes, that they no longer need to bother but can directly request data from the bank. Through this regulation, the Directorate General of Taxes of the Ministry of Finance has the flexibility to access financial information of customers who are taxpayers. Then, the legal consequences for banks are required to provide information to the Director General of Taxes, either through electronic/non-electronic or through other access and exchange of information. Banks or Financial Services Institutions that do not submit, do not carry out the procedures for this provision will have legal consequences for tax authorities, for banks and for customers